Isolation of extracellular vesicles from microalgae: towards the production of sustainable and natural nanocarriers of bioactive compounds. (23rd February 2021) - Picciotto, Sabrina; Barone, Maria E.; Fierli, David; Aranyos, Anita; Adamo, Giorgia; Božič, Darja; Romancino, Daniele P.; Stanly, Christopher; Parkes, Rachel; Morsbach, Svenja; Raccosta, Samuele; Paganini, Carolina; et al.
Abstract : Biophysical and biochemical characterisation of microalgae-derived extracellular vesicles. Abstract : Safe, efficient and specific nano-delivery systems are essential for current and emerging therapeutics, precision medicine and other biotechnology sectors. Novel bio-based nanotechnologies have recently arisen, which are based on the exploitation of extracellular vesicles (EVs). In this context, it has become essential to identify suitable organisms or cellular types to act as reliable sources of EVs and to develop their pilot- to large-scale production. The discovery of new biosources and the optimisation of related bioprocesses for the isolation and functionalisation of nano-delivery vehicles are fundamental to further develop therapeutic and biotechnological applications. Microalgae constitute sustainable sources of bioactive compounds with a range of sectorial applications including for example the formulation of health supplements, cosmetic products or food ingredients. In this study, we demonstrate that microalgae are promising producers of EVs. By analysing the nanosized extracellular nano-objects produced by eighteen microalgal species, we identified seven promising EV-producing strains belonging to distinct lineages, suggesting that the production of EVs in microalgae is an evolutionary conserved trait. Here we report the selection process and focus on one of this seven species, the glaucophyte Cyanophora paradoxa, which returned a protein yield in the small EV fraction of 1 μg of EV proteins per mg of dry weight of microalgal biomass (corresponding to 10 9 particles per mg of dried biomass) and EVs with a diameter of 130 nm (mode), as determined by the micro bicinchoninic acid assay, nanoparticle tracking and dynamic light scattering analyses. Moreover, the extracellular nanostructures isolated from the conditioned media of microalgae species returned positive immunoblot signals for some commonly used EV-biomarkers such as Alix, Enolase, HSP70, and β-actin. Overall, this work establishes a platform for the efficient production of EVs from a sustainable bioresource and highlights the potential of microalgal EVs as novel biogenic nanovehicles.